Occurence of ArmA and RmtB Aminoglycoside Resistance 16S rRNA Methylases in Extended-Spectrum β-Lactamases Producing Escherichia coli in Algerian Hospitals - Ayad, Amel; Drissi, Mourad; de Curraize, Claire; Dupont, Chloé; Hartmann, Alain; Solanas, Sébastien; Siebor, Eliane; Amoureux, Lucie; Neuwirth, Catherine (Frontiers in Microbiology, 2016)
The aim of this study was to characterize the extended-spectrum-β-lactamases (ESBLs) producing clinical strains of Escherichia coli isolated between January 2009 and June 2012 from Algerian hospitals and to determine the prevalence of 16S rRNA methylase among them. Sixty-seven ESBL-producers were detected among the 239 isolates included: 52 CTX-M-15-producers, 5 CTX-M-3-producers, 5 CTX-M-1-producers, 2 CTX-M-14-producers, 2 SHV-12-producers and one TEM-167-producer. Among the ESBL-producing strains twelve harboured 16S rRNA methylase genes: 8 rmtB and 4 armA. rmtB was located on a IncFIA plasmid and armA was located either on a IncL/M or a IncFIA plasmid. RmtB-producing isolates were genotypically related and belonged to the sequence type ST 405 whereas ArmA-producing isolates belonged to ST10, ST 167 and ST 117. This first description of 16S rRNA methylases among E. coli in Algerian hospitals pointed out the necessity to establish control measures to avoid their dissemination.